IMPLEMENTASI TAX AMNESTY TERHADAP PENERIMAAN PAJAK NEGARA DI KPP MADYA MAKASSAR - Haeruddin Haeruddin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
The aim of this research is to know the implementation of tax amnesty and tax revenue after the state used UU number 11, 2016 at KPP Madya Makassar. This research used descriptive qualitative method. After doing the analysis and discussion of the problem, the writer concludes that the implementation of tax amnesty is suitable with UU number 11 of 2016, and the revenue of state tax revenue was increase at KPP Madya Makassar.